Oral hairy Leukoplakia in HIV seropositive patient: literature review and case report - Milagres, Adrianna; Ramos, Ruth T.; Castiliano, Marília H.; Dias, Eliane P. (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: oral hairy leukoplakia (OHL) is a white lesion, nonremovable, most commonly on the lateral border of the tongue. Usually isasynmptomatic and treatment is not necessary. It is associated with severe immunodeficiency, and is considered a indicator of HIV infection andindicator of aids’s development and prognostic. Epstein-Barr virus is the causative agent, that causes nuclear changes in the keratinocytes (CA, GG,NB) Objective:. to realize a literature review and to relate a case of oral hairy leukoplakia in a patient infected with HIV. Methods: a aclinic exami-nation was realized and scraps from the lesions were obtained, fixed and stained by Papanicolaou technique. Results:the cytopathologic analysisshowed the nuclear changes and Candida sp.hiphaes, and the diagnoses was OHL associated with candidiases. Conclusion: OHL desappeared whenthe improvement of the imunologic status occour, with antiretroviral therapy. The diagnosis was made only when EBV or the nuclear changes wereidentified, than the cytopathology was a effective method, using the molecular methods only in doubtful cases.